A facile approach of micro-mesopores structure binder-free coin/monolith solid design activated carbon for electrode supercapacitor. (August 2021) - Apriwandi, Apriwandi; Taer, Erman; Farma, Rakhmawati; Setiadi, Rahmondia Nanda; Amiruddin, Erwin
Highlights: Banana leaves are firstly reported of high mesoporosity activated carbon. KOH-activation is facile approach to obtain porous carbon binder-free solid design. Mesoporosity can be controlled by different high pyrolysis temperature. A high capacitance of 245 f g   −   1 at symmetric supercapacitor. Abstract: A practical and effective approach is needed to obtain micro‑meso porous carbon in order to enhance electrode materials performance as energy storage applications. Therefore, this research aims at converting banana leaves biomass as a precursor into porous carbon via potassium hydroxide impregnation and physical activation at varying temperatures in the range of 700–900 °C. Most importantly, in this research, porous carbon is hierarchically prepared without complicated techniques such as hard/salt-templates, heteroatoms-doping, metal framework, or using graphene/metal oxides. Furthermore, the activated carbon is exhibited in the form of a binder-free coin/monolith solid design with the 3D porous structure clearly observed to determine the suitable micro/meso combinations. More importantly, activated carbon enhances the specific surface area of 623.491 m 2 g   −   1 using a high temperature and mesoporosity value of 46%. Therefore, the symmetric supercapacitor produced a high specific capacitance of 245 F g   −   1 in an acid electrolyte of 1 M H2 SO4 and 211 F g   −   1 in an alkaline electrolyte of 6 M KOH. The result showed that the hierarchical porous activated carbon based on banana leaf waste increases the specific energy by 34.67 Wh kg −1 with a specific power of 97.68 Wh kg −1 . In conclusion, this utilized an effectively feasible approach to obtaining biomass-based hierarchical activated porous carbon as an electrode material for energy storage devices. Graphical abstract: Image, graphical abstract